The effects of adding protein to dry-rolled sorghum grain fattening rations - DeGeer, C.V.; Smith, E.F.; Richardson, D.; Cox, R.F.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Previous work indicated sorghum grain fattening rations supplemented with 0.5 pound per head daily of soybean oil meal produced less efficient gains but carcasses about equal to those from heifers fed 1 pound of soybean oil meal per head daily. With each increase of 0.5 pound of protein (0.5 lb.-1.5 lbs.) came an increase in average daily gain and an increase in feed efficiency.
Keywords: Beef; Protein; Dry-rolled sorghum; Average daily gain